PERAN GURU AQIDAH AKHLAK DALAM MENINGKATKAN KEDISIPLINAN SHALAT DHUHA SISWA DI MADRASAH IBTIDAIYAH MUHAMMADIYAH GODOG POLOKARTO SUKOHARJO TAHUN PELAJARAN 2021/2022 - Desy Arianti,; Uswatun Khasanah,; Iffah Mukhlisah, (Journal of Innovation Research and Knowledge, 2022)
Desy Arianti, Uswatun Khasanah and Iffah Mukhlisah, Thesis, The Role of Moral Aqeedah Teachers in Improving The Discipline of Students’ Dhuha Prayer at Madrasah Ibtidaiyah Muhammadiyah Godog Polokarto Sukoharjo Academic Years 2021/2022 This study aims to determine: 1) The role of moral aqeedah teachers in improving the discipline of students' dhuha prayer at Madrasah Ibtidaiyah Muhammadiyah Godog Polokarto Sukoharjo in the 2021/2022 school year. 2) The supporting and inhibiting factors of the role of the moral aqeedah teacher in improving the student's dhuha prayer discipline at Madrasah Ibtidaiyah Muhammadiyah Godog Polokarto Sukoharjo in the 2021/2022 school year. This study uses a qualitative approach with a descriptive pattern. The research subjects were 2 teachers of aqidah morality and 22 students of grade 4 Madrasah Ibtidaiyah Muhammadiyah Godog Polokarto Sukoharjo. Methods of data collection using observation, interviews and documentation. To test the validity of the data using extended participation, observer persistence and triangulation. The data that has been collected is then analyzed with data reduction techniques, data presentation, and drawing conclusions. The results of the study show that: 1) The role of the aqeedah moral teachers in improving the student's dhuha prayer discipline includes the teacher's role as a motivator, the teacher as a mentor, the teacher as a demonstrator and the teacher as a corrector. 2) The supporting factors in improving the student's dhuha prayer discipline include adequate facilities and infrastructure as well as cooperation between teachers. Inhibiting factors in improving students' dhuha prayer discipline include student personality, limited time for dhuha prayer, and environment or student association.